A fluid dynamic gauging device for measuring biofilm thickness on cylindrical surfaces - M. Lemos (2016)
Many industrial processes are susceptible to biofouling. The thickness and structure of such biofilms arekey factors in the design of effective cleaning strategies. A novel method based on fluid dynamic gauginghas been developed for measuring the thickness and the shear stress needed for removal of the biofilmsformed on cylindrical surfaces. The device operates with the test cylinder immersed in liquid: liquid iswithdrawn or ejected from a nozzle located near the biofilm surface. There is no net change of liquidvolume, making it ideal for sterile and aseptic operation and for studies using valuable liquids. Biofilmremoval may also be tested by using appropriate hydrodynamic conditions.Calibration tests using ejection and suction flows in the laminar regime (Reynolds number around100) indicated a measurement accuracy of ±19 m and showed good agreement with computationalfluid dynamics simulations. The device was commissioned in tests on Pseudomonas fluorescens biofilmsformed on high density polyethylene (HDPE) and stainless steel (SS) cylinders of diameter 25 mm underconditions of mild shear stress (around 2 Pa in these tests). The biofilm thickness was not uniform tothe eye and measurements made over the surface of the test cylinders confirmed this: layer thicknessesranged from effectively 0-300 m. The biofilms formed on HDPE were thicker than those formed on SS.